Corrosion Resistance and Biological Properties of Pure Magnesium Modified by PEO in Alkaline Phosphate Solutions (2023)
ABSTRACT: Magnesium (Mg) has been explored during the last few decades in the biomedical industry as a biodegradable implant. However, mechanical properties and corrosion resistance are still big concerns for clinical use. Therefore, this study proposes a suitable surface modification of the Mg by plasma electrolytic oxidation (PEO) to improve its corrosion resistance and biological performance. Mg samples were processed in a galvanostatic mode using an electrolytic solution of a phosphate compound supplemented with either potassium pyrophosphate or sodium-potassium tartrate. The obtained coatings were physiochemically characterized by SEM, XRD, EDS, and micro-Raman spectroscopy. The corrosion resistance of the coatings was studied using a hydrogen evolution setup and electrochemical tests. Finally, the biological performance of the material was evaluated by using an indirect test with osteoblasts. Obtained coatings showed a porous morphology with thicknesses ranging from 2 to 3 µm, which was closely dependent on the PEO solution. The corrosion resistance tests improved the degradation rate compared to the raw material. Additionally, an unreported active–passive corrosion behavior was evidence of a protective layer of corrosion products underneath the anodic coating. Indirect in vitro cytotoxicity assays indicated that the coatings improved the biocompatibility of the material. In conclusion, it was found that the produced coatings from this study not only lead to material protection but also improve the biological performance of the material and ensure cell survival, indicating that this could be a potential material used for bone implants.